Efeito do hidrogel em diferentes profundidades com mulching como cobertura do solo e influência de lâminas de irrigação no cultivo do pepineiro irrigado - Frazão, Diogo Sales (2024)
Vegetable cultivation plays a fundamental role in food security and the global economy. Among these vegetables, cucumber (Cucumis sativus L.) stands out as a versatile crop widely consumed worldwide. In modern agriculture, the search for innovative methods to enhance productivity and ensure efficient use of natural resources is constant. Techniques such as hydrogel application, mulching, and irrigation levels have gained prominence as promising strategies for making crop cultivation more efficient, promoting better results in water and nutrient management, which can lead to higher yields and sustainability in crop production. Therefore, this study aimed to evaluate the effects of using hydrogel at different soil depths, combined with mulching and different irrigation levels, on the development and productivity of irrigated cucumber. The experiments were conducted from August 1, 2023, to October 18, 2023, in the experimental area of the Agrometeorological Station of the Federal University of Ceará, Brazil. The soil in the experimental areas is classified as sandy clay loam. The study was conducted using the hybrid cucumber HS-1020 Chile. The irrigation system used in the experiments was a localized drip system. The area of each experiment was 107.52 m². The first experiment aimed to evaluate the effect of hydrogel at different depths, combined with mulching as soil cover. The treatments were: no hydrogel (SEMH); hydrogel at 15 cm depth (H15); hydrogel at 30 cm depth (H30); hydrogel at 15 cm depth and mulching (H15+M); and hydrogel at 30 cm depth and mulching (H30+M). The second experiment consisted of applying irrigation levels based on the Penman-Monteith ETo (EToPM) parameterized by FAO, corresponding to the treatments: Li30 – 30% EToPM; Li60 – 60% EToPM; Li90 – 90% EToPM; Li120 – 120% EToPM; and Li150 – 150% EToPM. The experimental design used was a randomized block design, consisting of five treatments and five blocks. One cycle of irrigated cucumber was conducted, with two harvests: the first occurred 15 days after the first fruit appeared, and the second 15 days after the first harvest. The treatments in the first experiment had a significant effect on the variables: number of fruits (NF), water use efficiency (EUA), and productivity (Prod). The treatments that showed statistically higher productivity were H30 and H30+M. The irrigation levels tested had a significant effect on the variables: pulp thickness (EP), number of fruits (NF), water use efficiency (EUA), and productivity (Prod), adjusting to a second-degree polynomial model. The irrigation level that maximized cucumber productivity was estimated at 108% of EToPM, for the climatic conditions of the 2023 crop.